Desenvolvimento do feijão-caupi em função do fornecimento de nitrogênio via FBN eou adubação mineral em solo de savana de Roraima - Carvalho, Kelter Santos (2011)
The Biological nitrogen fixation (FBN) brings great benefits to tropical soils by increase their availability and productivity of crops. Objectified if with this work to assess the development of Cowpea in function of the supply of nitrogen via FBN and/or mineral fertilization on soil savanna of Roraima. The experiment was conducted in house of vegetation in Center of Agrarian Sciences, in Boa Vista, Roraima-Brazil, using hard polyethylene vases with 5 L soil collected on layer 0 – 20 cm. the experimental design was in blocks blocks in schema factorial (5 x 5), five classes of soil are representative of ecosystem of Savannah Yellow Latosol, Distrocoeso (LAdx), Red Latosol Dystrophic (LVd), typical Argisols Yellow Distrocoeso (PAdx) argisols, red yellow Dystrophic (PVAd) and Neossolo Flúvico Typical Psamítico (RYve) and five doses of fertilization, being four-0, 20, 40 and 80 kg ha-1of N in inoculated plants and a – 0 kg ha-1 of N in plants inoculated with four repetitions. The cowpea seeds of the plant variety BRS Guariba were inoculated with the strain of Bradyrhizobium BR 3262. Assessed-if the components of production (number, size and weight of pod), dry mass, number of root nodules and dry mass of nodules. Inoculation has resulted in an increase in the variables studied in all soils studied. Doses of N in inoculated plants provided significant increments ranging from solo classes, from 3 to 18% in the components of production and from 8 to 70% for the other variables. Depending on the dose of N fertilization does not affect negatively the nodulation in cowpea.